Emigrating peasants and returning emigrants: emigration with return in a Portuguese village - Reis, M.; Gil Nave, J. (Sociologia Ruralis, 1986)
On the basis of a study carried out in a village in the interior of rural Portugal, this article attempts to distinguish the elements of a peasant strategy of emigration centred upon the development and expansion of the family agricultural holding through earnings obtained from work in France, which has as its medium term aim return to the rural community. Priority is given to the observation of the social practices of actors in the emigration process, through the reconstitution of individual and family trajectories of returnees, or those in the process of doing so. The impact of their social and economic investment in the rural community is also considered. We conclude that emigration with return is directed towards the remodelling of local structures. Recourse is had to specific forms of relation with work abroad, amongst which the departure of the household head alone and seasonality in the final phase of emigration are distinguished. The practice of pluri-activity based on two quite distinct and distant socio-geographical contexts, makes viable a rural area which would otherwise have long been compromised through the process of social and demographic bleeding to which it was subjected.